Solvation-Assisted Young’s Modulus Control of Single-Crystal Fullerene C𝟕𝟎 Nanowhiskers - Tokushi Kizuka; Kun'ichi Miyazawa; Takayuki Tokumine (Journal of Nanotechnology)
Single-crystal nanowhiskers (NWs) composed of fullerene C70 molecules were synthesized by the liquid-liquid interfacial precipitation method that used m-xylene as a saturated solution of C70 molecules. Bending behavior of the individual NWs was observed by in situ transmission electron microscopy equipped with nanonewton force measurements using an optical deflection method. The Young’s modulus of the NWs was estimated to be 0.3–1.9 GPa, which was 2–7% of the moduli of fullerene NWs with similar diameters synthesized using other solvents, that is, toluene and pyridine. The influence of the solvent used in the precipitation method on Young’s modulus is discussed.